Study protocol: a randomised, controlled trial of a nurse navigator program for the management of hepatitis C virus in patients with severe mental disorder - Quemada-González, Casta; Morales-Asencio, José Miguel; Hurtado, María M.; Martí-García, Celia (BMC Springer Nature, 2022)
Background To evaluate the impact of a nurse navigation program on treatment adherence and resolution of hepatitis C infection in patients with severe mental disorder. Methods An open, randomized, controlled trial with blinded outcome assessment. The intervention group will engage in a nurse navigation program designed by mental health nurses. The program involves active screening for patients with severe mental disorder. The patients and caregivers included in the program will receive information, training, support and guidance throughout the treatment and recovery process, which involves different healthcare professionals and units. The control group will receive the standard of care, which includes follow-up by a family physician, referral to the hepatologist, serological testing, new referral to the hepatologist, onset of treatment, and follow-up. Multidisciplinary care will be provided along a coordinated and seamless clinical pathway led by a nurse navigator. The primary endpoints are total recovery (hepatitis C cure) and treatment adherence. Occurrence of symptoms of schizophrenia and health-related quality of life will be also recorded. Follow-up of patients will be performed three and six months after the administration of antiviral treatment. The study was authorised by the Ethics Committee of Malaga in December 2021. Funding was approved in March 2021. Discussion If this intervention is proven to be effective in improving treatment access and adherence, it will represent a step forward in addressing a chronic health issue that is 16 times more prevalent in the population with severe mental disease. Finally, this intervention may lead to the detection of undertreated HCV infection in this population of patients.
Keywords: Hepatitis C; Mental disorders; Critical pathways; Patient care planning; Nursing